The Poet as a Crusader for Social Justice: Stylistic Implications in Niyi Osundare’s Random Blues - Anthony Ebebe Eyang; Emmanuel Israel Archibong (Fakultas Sastra - Universitas Muslim Indonesia, 2021)
The role of the poet as a crusader for social justice has been well-acknowledged in literary circles and beyond. This stems from the nature of art as a humanistic endeavor genetically imbued with the spirit of standing with humanity and freeing it from the stranglehold of social malfeasance, reprehensible and tendencious inclinations. Poetry is, therefore, a unique artistic expression of solidarity with the people and an aspiration or vision towards a better human experience. Osundare’s social involvement through literary practice has meant the engagement of issues with the intent of exposing the contradictions that impoverish society. The social involvement and foregrounding of the thematic issues has entailed the mobilization of linguistic resources as stylistic strategies for poignancy and effective communication. This paper interrogates the meeting point between Osundare’s social concerns in his Random Blues and the linguistic strategies he employs to the service of poetic communication. To this end, the paper analyses New Historicism which underscores the invocation of socio-political times in the production and interpretation of literature; and insights from Systemic Functional Linguistics that stress the place of function and relevance in determining linguistic choice and meaning. The paper concludes that as a social critic, Osundare has used poetry to spearhead a rude awakening of the oppressed in the society against the contradictions and manipulations by the powerful few, calling the latter to action and championing the cause to bring about social transformation and liberation from the chokehold of tyranny and oppression.